The mortality patterns of lung cancer between 1990 and 2013 in Xuanwei, China. Issue 2 (November 2015) - Chen, Gongbo; Sun, Xin; Ren, Hongyan; Wan, Xia; Huang, Hecang; Ma, Xiangyun; Ning, Bofu; Zou, Xiaonong; Hu, Weijiang; Yang, Gonghuan
Highlights: Mortality rate of lung cancer increased from 34/10 5 to 105/10 5 between 1990 and 2013. Gap of lung cancer mortality is widening between Xuanwei and rural areas of China. Ratio of lung cancer mortality rate among males to that among females is 1.1–1.3. 45Q15 of lung cancer is 5–7 times higher than that of national average. Regional concentration of lung cancer mortality did not change between 1990 and 2013. Abstract: Objectives: To explore the variations in the mortality trends, especially death due to lung cancer, from 1990 to 2013 in Xuanwei City. Materials and methods: Mortality data were collected in Xuanwei during the 2nd and 3rd National Retrospective Sampling Survey on Mortality and Routine Death Registration System (DRS) during 2011–2013. According to the result of the survey on under-reported deaths, mortality data from DRS during 2011–2013 were adjusted. Disease specific mortality rate, age-standardized mortality rate (ASMR) and 45Q15 were calculated in Xuanwei and compared with those in rural areas of China. Results: During three periods, 1990–1992, 2004–2005 and 2011–2013, lung cancer contributed to 56.86%, 58.45% and 63.03% of deaths from all cancers respectively with a much higher proportion than rural areas nationally. The ASMR of lung cancer for males surged from 41.43/10 5 to 88.17/10 5 during 1990–2005 and it surged from 37.70/10 5 to 74.45/10 5 for females. Although they declined slightly during 2011–2013 (82.53/10 5 and 62.62/10 5 for males and females respectively), the ASMR of lung cancer among males in Xuanwei was three times of that in rural areas in China, and it was six times higher among females. The 45Q15 of lung cancer for males in Xuanwei was 3–5 times of that in rural areas of China and for females it was 7–9 times. The high-mortality areas of lung cancer were still located in Laibin, Longchang, Wanshui and Shuanglong Communities. High-mortality areas of lung cancer expanded to their surrounding areas and those in southeast. Conclusions: Although indoor air pollution caused by smoky coal has been fairly well controlled, patterns of death due to lung cancer have not obviously changed. The mortality rate of lung cancer among females was similar to that among males. Therefore, further studies should be conducted to comprehensively explore the risk factors of lung cancer in Xuanwei.